Deformations in the Shoulder Tissues During Load Carriage: A Computational Model. (November 2015) - Hadid, Amir; Belzer, Noa; Shabshin, Nogah; Epstein, Yoram; Gefen, Amit
Abstract : Abstract: Hadid, A, Belzer, N, Shabshin, N, Epstein, Y, and Gefen, A. Deformations in the shoulder tissues during load carriage: a computational model. J Strength Cond Res 29(11S): S144–S148, 2015—Shoulder soft tissue deformations seem to be one of the limiting factors of load carriage among soldiers and recreational backpackers that are required to carry heavy loads. Yet, there are no loading limits related to the forces borne by the shoulders, and the backpacks designs are not consistent with providing pressure relief from this sensitive anatomical region. The aim of this study was to develop a model that will enable to study the biomechanical loads that develop in the shoulder under heavy loads and to help in optimizing load carriage systems design. A 3-dimensional, anatomically accurate finite element model of a human shoulder was constructed based on MRI scans. The model was developed to calculate the effective stresses on the skin below the shoulder strap (superficial loads) and the effective strain in the brachial plexus region (inner tissue deformation) for loads of up to 35 kg. The model successfully predicted deformations in the soft tissue surrounding the brachial plexus when compared with deformations measured from load-bearing MRI scans. The model yielded a skin pressure mapping, which showed pressure hotspots in the clavicle region. Inner tissue deformations mapping, as assessed by brachial plexus envelop strains, were found to peak at 30% effective strain at the lateral aspect below the pectoralis muscle. The newly developed model successfully predicted soft tissue deformations in the shoulder related to backpacks. This model can be used to optimize load carriage systems for better distribution of pressure over the shoulders and lower inner tissue deformations.